Brain and spinal tumours in children aged under two years: incidence and survival in Britain, 1971-85. - Stiller, C. A. (Nature Publishing Group, 1992)
There were 548 children aged under two with brain and spinal tumours diagnosed during 1971-85 in Great Britain and included in the population-based National Registry of Childhood Tumours. Children aged under two accounted for 12% of all children registered with tumours in these sites. The annual incidence was 25.0 per million. Ependymoma, astrocytoma and medulloblastoma (including primitive neuroectodermal tumour) each accounted for around a quarter of the total. Five-year survival rates were 20% for ependymoma, 43% for astrocytoma and 13% for medulloblastoma, each significantly lower than for children aged 2-14 in the corresponding diagnostic group. Mortality in the first year after diagnosis was very high but there were also substantial numbers of later deaths. There was no significant trend in survival rates during the period under review.